2009
DOI: 10.1007/s15010-009-8342-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of colistin for the treatment of multidrug-resistant Pseudomonas aeruginosa infections

Abstract: Colistin is a safe option for the treatment of MDRP infections, with acceptable clinical outcomes. However, bacteriological eradication is difficult to achieve, especially in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 25 publications
6
59
0
Order By: Relevance
“…By contrast, in this study, higher doses of colistin were not related to a better clinical outcome. However, clinical response rate was similar to those reported by other authors [2,[25][26][27][28]. These results could be explained in part by the fact that only 16 patients had received higher CMS doses (3 million IU every 8 hours).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…By contrast, in this study, higher doses of colistin were not related to a better clinical outcome. However, clinical response rate was similar to those reported by other authors [2,[25][26][27][28]. These results could be explained in part by the fact that only 16 patients had received higher CMS doses (3 million IU every 8 hours).…”
Section: Discussionsupporting
confidence: 89%
“…The reported rate of colistin-associated nephrotoxicity varies from 0% to 37% in older studies [2,3,20,21]. This variability could be the result of differences in the definitions of nephrotoxicity and in the dose and duration of treatment with CMS in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections with carbapenem-resistant P. aeruginosa generally have a poorer prognosis than infections with carbapenem-sensitive P. aeruginosa (7). In addition, the efficacy of colistin against infections with carbapenem-resistant P. aeruginosa has not been established (8). Appropriate use of antimicrobial drugs is required to control the emergence of drug-resistant bacterial pathogens (9,10).…”
mentioning
confidence: 99%
“…2,4) Colistin was originally developed in Japan in the 1940s-1950s; however, initial studies reported adverse reactions, including nephrotoxicity or peripheral nervous system disorders. 5) Because of these adverse events and the introduction of safer antibiotics, clinical use of colistin was abandoned in Japan in 1990.…”
mentioning
confidence: 99%